Exploring the Palmar Surface: A Critical Case Report for Emergency Physicians - Matthew Van Ligten; Douglas E. Rappaport; Wayne A. Martini (Clinical Practice and Cases in Emergency Medicine)
Introduction: Tendon injuries of the hand present a diverse spectrum of challenges in emergency medicine, ranging from minor strains to catastrophic ruptures. The superficial anatomy of hand tendons predisposes them to various mechanisms of injury, leading to complex medical scenarios. Here, we present a unique case of flexor tendon exposure secondary to abscess formation and spontaneous rupture, emphasizing the importance of prompt recognition and management of such injuries in the emergency department. Case Report: A 69-year-old male with multiple comorbidities presented with diffuse pain and a pale, pulseless right lower extremity, alongside a left hand exhibiting exposed flexor tendons due to recent abscess drainage. Despite broad-spectrum antibiotics and pain management, the patient underwent above-knee amputation due to vascular compromise. Evaluation revealed a complete flexor tendon rupture likely attributable to infection, necessitating emergent hand surgery at the bedside. Conclusion: Understanding the nuances of tendon injuries is paramount for emergency physicians, given their potential for lifelong disability if inadequately addressed. Awareness of risk factors and appropriate management strategies, including early surgical intervention when indicated, is essential in optimizing patient outcomes. This case serves as a reminder of the complexities involved in hand injuries and underscores the need for vigilance and tailored care in the emergency setting.